1989
DOI: 10.1099/0022-1317-70-12-3421
|View full text |Cite
|
Sign up to set email alerts
|

Host-dependent Suppression of Temperature-sensitive Mutations in Tobacco Mosaic Virus Transport Gene

Abstract: SUMMARYTobacco mosaic virus (TMV) mutants Lsl and Ni2519, temperature-sensitive (ts) in transport function in tobacco plants, were able to spread at high temperature (33 °C) in Amaranthus caudatus L. plants. On the other hand, TMV ts coat protein mutants retained the ts phenotype in both host plants. The ability of Lsl and Ni2519 to spread systemically in A. caudatus at high temperature is probably due to the functional stabilization of the transport proteins by a factor(s) provided by the host plant. In accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Previous reports showed that LS1 was TS in all plants tested except A. caudatus, also a plant with C4 metabolism (9,16). To date, we have been unable to repeat these observations using a similar experimental protocol (C.J.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…Previous reports showed that LS1 was TS in all plants tested except A. caudatus, also a plant with C4 metabolism (9,16). To date, we have been unable to repeat these observations using a similar experimental protocol (C.J.…”
Section: Discussionsupporting
confidence: 44%
“…French, unpublished data); the reasons for this discrepancy are under investigation. Therefore, no generalizations can be made on an association of C4 metabolism with putative host stabilizing factors at nonpermissive temperatures (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It occurs when the gene product of both viruses is a multimeric protein and each virus is defective in different domains of the functional viral protein (Fincham, 1966). Complementation in mixed infections of plant viruses has been suggested (Dodds and Hamilton, 1976;Mushegian et al, 1989), but has not been extensively used with most RNA plant viruses for genetic analysis.…”
Section: Discussionmentioning
confidence: 99%